Pork proteins oxidative modifications under the influence of varied time-temperature thermal treatments: A chemical and redox proteomics assessment. (June 2018) - Mitra, Bhaskar; Lametsch, Rene; Akcan, Tolga; Ruiz-Carrascal, Jorge
Abstract: The impact of thermal processing on meat proteins oxidation was investigated. Cooking treatments included 58 °C for either 72 min or 17 h (mimicking low temperature-long time sous vide cooking), 80, 98 and 160 °C for 72 min (mimicking common cooked meat products, stewing and roasting, respectively) and 118 °C for 8 min (autoclaving). Tryptophan degradation, fluorescent oxidation products, free thiol content and α-aminoadipic and γ-glutamic semialdehydes were tracked. For all of them, there was a consistent trend to increased levels of oxidative damage with higher cooking temperatures and longer cooking times, although the extent varied from one indicator to another. Through proteomics, peptide oxidative modifications like carbonylation, malonaldehyde adducts and hydroxykynurenin (tryptophan oxidation products) were also detected at residue level. Our findings indicate that protein oxidation is dependent upon the heat treatment, which point out to a different effect on the nutritional quality of proteins in meat products. Highlights: Oxidative modifications of pork proteins under different heat treatments were studied. Protein oxidation markers increased with higher cooking temperature and time. Oxidative residue level protein modifications were identified. Different proteins showed a different extent of oxidative damage at the residue level.